Pengembangan Model Mitigasi Resiko Kredit Berbasis Komputasional Untuk Meningkatkan Kemampuan Manajemen Resiko Bagi Koperasi - Wahyono, Teguh; Cahyono, Ariya Dwika (Jurnal Sistem Komputer, 2015)
Cooperative lending is financial credit which provide benefits to the both cooperative and the customers. In the provision of credit, the cooperative should consider the customerâ€™s ability to meets its obligations through the six criteria; character, collateral, condition, capacity, capital, and area. This study aims to develop an credit risk mitigation model based on Computational Science to improve risk management for Cooperative. In this case, bayesian algorithm do statistical calculation depend on six criteria. The major advantages of the proposed system are higher precision in credit evaluation of the high risk customers and higher sensitivity in the evaluation of higher value loans.Â